Digital Pneumatology: The Relevance and Role of the Holy Spirit in Technological Society - Putrawan, Bobby Kurnia; Ayuk, Ayuk Ausaji (Perkumpulan Teolog Agama Kristen Indonesia, 2025)
The rapid advancement of digital technology has transformed human interaction, communication, and spirituality, creating new challenges and opportunities for theology. In this changing landscape, understanding how the Holy Spirit works within digital culture becomes essential for a relevant pneumatological reflection. The purpose of this study is to explore the relevance and role of the Holy Spirit in a technologically mediated society, emphasizing the Spirit’s continuing work in renewing creation and guiding human life. This study employs a contextual theological analysis that integrates systematic theology, biblical interpretation, and digital ethics to examine how pneumatology interacts with the realities of virtual presence and communication. Through a qualitative, literature-based approach, it synthesizes classical and contemporary theological insights to construct a model of “digital pneumatology.” The findings indicate that the work of the Holy Spirit remains active in digital spaces—empowering believers to experience communion, truth, and transformation beyond physical boundaries. The Spirit sanctifies technology, transforming digital platforms into instruments of grace and moral discernment. Consequently, digital pneumatology affirms that divine presence continues to inspire creativity, mission, and ethical responsibility within modern technological culture. This reflection offers vital implications for the church’s ministry and the spiritual formation of believers in the twenty-first century. Contribution: This study contributes to digital theology by articulating how the Holy Spirit remains active and transformative within technological culture. It offers a theological framework that integrates pneumatology with digital ethics, emphasizing the Spirit’s role in sanctifying technology and shaping authentic Christian spirituality in the digital era. Kemajuan pesat teknologi digital telah mengubah interaksi, komunikasi, dan spiritualitas manusia, menciptakan tantangan sekaligus peluang baru bagi teologi. Dalam lanskap yang terus berubah ini, pemahaman tentang bagaimana Roh Kudus bekerja di dalam budaya digital menjadi sangat penting bagi refleksi pneumatologis yang relevan. Tujuan dari penelitian ini adalah untuk mengeksplorasi relevansi dan peran Roh Kudus dalam masyarakat yang dimediasi oleh teknologi, dengan menekankan karya Roh yang terus-menerus dalam memperbarui ciptaan dan menuntun kehidupan manusia. Penelitian ini menggunakan analisis teologi kontekstual yang mengintegrasikan teologi sistematik, penafsiran biblika, dan etika digital untuk menelaah bagaimana pneumatologi berinteraksi dengan realitas kehadiran dan komunikasi virtual. Melalui pendekatan kualitatif berbasis kepustakaan, penelitian ini mensintesis wawasan teologis klasik dan kontemporer untuk membangun sebuah model “pneumatologi digital.” Temuan penelitian menunjukkan bahwa karya Roh Kudus tetap aktif dalam ruang-ruang digital—memberdayakan orang percaya untuk mengalami persekutuan, kebenaran, dan transformasi melampaui batas-batas fisik. Roh Kudus menguduskan teknologi, mengubah platform digital menjadi sarana anugerah dan penilaian moral. Dengan demikian, pneumatologi digital menegaskan bahwa kehadiran ilahi terus menginspirasi kreativitas, misi, dan tanggung jawab etis dalam budaya teknologi modern. Refleksi ini memberikan implikasi penting bagi pelayanan gereja dan pembentukan spiritual orang percaya di abad ke-21. Kontribusi: Penelitian ini memperluas kajian teologi digital melalui perumusan kerangka yang mengintegrasikan pneumatologi dan etika digital, menegaskan karya Roh Kudus yang terus aktif dalam menguduskan teknologi dan membentuk spiritualitas Kristen di era digital.